TRICUSPID VALVE DYSFUNCTION AFTER ORTHOTOPIC HEART TRANSPLANTATION - S.Y. Shemakin; T.A. Khalilulin; A.A. Fedoseeva (Вестник трансплантологии и искусственных органов, 2009)
There’s an estimation of tricuspid dysfunction detection of various degrees in posttransplant period depending on operation technique. The article presents the dependence of development tricuspid dysfunction up to 1 st. degree from the level of transpulmonary gradient, which is integrated index of pulmonary hypertension level and which doesn’t change over postransplant period. In this research tricuspid dysfunction of 2–3 degrees most frequently detected in the remote period after heart transplantation or was the result of any postransplant complication.